2007
DOI: 10.1111/j.1600-0579.2007.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health behaviour and its determinants amongst Iranian dental students1

Abstract: Education and training in preventive measures should be effective enough to overcome background characteristics. There is room for improving the OHB of Iranian dental students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
73
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 28 publications
21
73
8
Order By: Relevance
“…4 Whereas according to Khami, positive dental health attitudes in females can be explained on the basis that females are more concerned about their body and appearance and would tend to be visiting the dentist more often. 9 More number of participants in group A used to visit the dentist for regular check-up when compared to group B, and majority group B population visited the dentist only when they had a toothache. Which was similar to the finding across the three cultures (Japan, Hong Kong and China) where more than half the students put off going to the dentist until they had a toothache.…”
Section: Male/femalementioning
confidence: 99%
“…4 Whereas according to Khami, positive dental health attitudes in females can be explained on the basis that females are more concerned about their body and appearance and would tend to be visiting the dentist more often. 9 More number of participants in group A used to visit the dentist for regular check-up when compared to group B, and majority group B population visited the dentist only when they had a toothache. Which was similar to the finding across the three cultures (Japan, Hong Kong and China) where more than half the students put off going to the dentist until they had a toothache.…”
Section: Male/femalementioning
confidence: 99%
“…The oral Major differences in oral health knowledge and behavior in a group of Iranian pre-university students: a cross-sectional study Hossain Neamatollahi 1) , Masoumeh Ebrahimi 1) , Maryam Talebi 1) , Mana H. Ardabili 2) and Keiwan Kondori Original health knowledge and behavior varied with the major subject of study (18,19), gender (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and culture (18,20,21). The role of education level in preventive measures has also been confirmed by several studies (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiologic studies showed that girls exhibited better oral health behavior than boys (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The oral Major differences in oral health knowledge and behavior in a group of Iranian pre-university students: a cross-sectional study Hossain Neamatollahi 1) , Masoumeh Ebrahimi 1) , Maryam Talebi 1) , Mana H. Ardabili 2) and Keiwan Kondori Original health knowledge and behavior varied with the major subject of study (18,19), gender (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and culture (18,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…10,11,12 However, no studies have sought to relate the acquisition of knowledge (one of the constituents of the initial education tool) with the adoption of measures related to self-care practices.…”
Section: Introductionmentioning
confidence: 99%